The Effect of Endorsers' Source Credibility on Emotion Towards Youtube's Advertisement - Dwi Agitashera; Nuke Farida; Rika Wulandari (ULTIMA Comm, 2020)
This study examines the effect of endorsers' source credibility on emotion towards youtube's advertisement. We analyze the impact of social media influencer and celebrity's credibility on emotional responses of respondents, namely pleasure and arousal. The data were collected by a survey through google form related to source credibility and S-O-R theory. Three hundred and eighty-five people joined the survey distributed via Google Form. The amount of respondent is 385 people using Lemeshow formula with a Margin of Error 5% and purposive sampling technique. The study used Multivariate Regression Analysis and Independent Sample T-Test. Findings showed that there is a significant effect of social media influencer and celebrity's credibility to emotional pleasure and arousal towards the advertisement. It is also found that social media influencer's expertise influenced stronger on pleasure and arousal than attractiveness and trustworthiness. In the other hand, celebrity's trustworthiness has a stronger impact on emotion pleasure and arousal than attractiveness and expertise. We suggested that future research can also analyze purchase intention because some previous studies stated that emotional response could predict purchase intention. Key Word: source credibility, celebrity, social media influencer, emotional responses